2003
DOI: 10.1172/jci19773
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-specific modification of genomic DNA by small DNA fragments

Abstract: Small DNA fragments have been used to modify endogenous genomic DNA in both human and mouse cells. This strategy for sequence-specific modification or genomic editing, known as small-fragment homologous replacement (SFHR), has yet to be characterized in terms of its underlying mechanisms. Genotypic and phenotypic analyses following SFHR have shown specific modification of disease-causing genetic loci associated with cystic fibrosis, β-thalassemia, and Duchenne muscular dystrophy, suggesting that SFHR has poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 45 publications
2
55
0
Order By: Relevance
“…9 Short DNA fragments (SDFs) have also been used for catalyzing gene correction in a process labeled short fragment homologous recombination (SFHR). 29 SDFs are generated as PCR products with a typical length between 100 and 600 base pairs. The mechanism of action is unclear but considering the heterogeneity of the vector, it is not unlikely that it follows a similar pathway as oligonucleotides (see below).…”
Section: Single-stranded Dna Catalyzes Gene Repair Most Effectivelymentioning
confidence: 99%
“…9 Short DNA fragments (SDFs) have also been used for catalyzing gene correction in a process labeled short fragment homologous recombination (SFHR). 29 SDFs are generated as PCR products with a typical length between 100 and 600 base pairs. The mechanism of action is unclear but considering the heterogeneity of the vector, it is not unlikely that it follows a similar pathway as oligonucleotides (see below).…”
Section: Single-stranded Dna Catalyzes Gene Repair Most Effectivelymentioning
confidence: 99%
“…'Genome editing' with this new meaning was first used at the beginning of the 2000s (Balbas and Gosset 2001;Stark and Akoplan 2003;Gruenert et al 2003), and the expression progressively became more widespread in subsequent years. The main researchers involved in the development of these new tools, such as Dana Carroll and Srinivasan Chandrasegaran (Durai et al 2005;Carroll 2008), were far from being the strongest supporters of the new vocabulary.…”
Section: Editing the Genomementioning
confidence: 99%
“…Furthermore, a method for altering desired genomic DNA sequences in human somatic cells could lead to a gene therapy approach for diseases caused by genetic alterations (gene correction). For example, the dystrophin gene in Duchenne muscular dystrophy patients and the cystic fibrosis transmembrane conductance regulator gene in cystic fibrosis patients are potential targets of this technology (Gruenert et al, 2003). Targeted sequence conversion using oligonucleotides has been developed for introducing small sequence alterations including deletions, insertions, and base-substitutions into mammalian genomic DNA (Andersen et al, 2002;de Semir and Aran, 2006;Igoucheva et al, 2004;Parekh-Olmedo and Kmiec, 2007;Richardson et al, 2002;Seidman and Glazer, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Targeted sequence conversion using oligonucleotides has been developed for introducing small sequence alterations including deletions, insertions, and base-substitutions into mammalian genomic DNA (Andersen et al, 2002;de Semir and Aran, 2006;Igoucheva et al, 2004;Parekh-Olmedo and Kmiec, 2007;Richardson et al, 2002;Seidman and Glazer, 2003). Small double-stranded DNA fragments have also been used to modify genomic DNA in both human and mouse cells (Gruenert et al, 2003;Sangiuolo, F. and Novelli, 2004). We recently found that a tailed duplex (TD) fragment, prepared by annealing an oligonucleotide to a several-hundred-base single-stranded (ss) DNA fragment, converted a target sequence in cultured mammalian cells with a higher efficiency than did a conventional double-stranded DNA fragment (Tsuchiya, et al, 2008).…”
Section: Introductionmentioning
confidence: 99%